THE CONCEPT OF “FREEDOM” IN SPAIN (1770-1870) - Chacón Delgado, Pedro José (Revista de Historia Social y de las Mentalidades, 2024)
As a consequence of the revolutionary events in Cadiz, the concept of ‘liberty’ in Spain became one of the clearest distinguishing marks of political modernity. It would be the nucleus around which to a great extent political debate and the country’s public life as a whole would henceforth revolve. The conflict regarding its meaning would form an essential part of political combat and ideological demands amongst not only those forces fighting for a more or less drastic change in the Old Regime, but also those who continued to defend it from a constitutionalist standpoint. This work details the changes in meaning of the concept of liberty and its different uses in conjunction with the various adjectives which define it (natural, civil, political, etc) throughout political history and the diverse ideological options which arose during each of the historical subperiods which constituted the cycle 1770-1870.